Nutrition for sport and exercise - Dunford, Marie; Doyle, J. Andrew (Cengage, 2019)
Nutrition for Sport and Exercise is designed primarily as a college-level text for upper-division courses in sports nutrition. It carefully illustrates the links among exercise, nutrition, and the ultimate goal which are recovery, optimal performance, and good health. In addition to explaining the rationale behind the recommendations made to athletes, the text helps instructors and students translate these recommendations to specific plans for the appropriate amount and type of foods, beverages, and/or supplements to support training, recovery, and performance. First and foremost, this book is scientifically sound and evidence based, but it is also filled with practical nutrition information and designed so faculty can easily teach from the text